PHENOMENOLOGICAL APPROACH TO THE USE OF SOCIAL MEDIA AMONG BPI IAIN BONE STUDY PROGRAM STUDENTS: A COMMUNICATION PSYCHOLOGY PERSPECTIVE - Baharuddin, Baharuddin; Utami, Sari (Al-Mubin, 2025)
The phenomenological approach in this research is to understand individual experiences in using social media. In the context of communication psychology, this research will look at how students perceive social media use, as well as how this experience affects their social interactions and psychological well-being. This research will use a qualitative phenomenological approach. The research sample will consist of students from the BPI IAIN Bone study program who actively use social media. Data collection will be carried out through in-depth interviews and participant observation. The collected data will be analyzed using an inductive approach to identify themes and patterns that emerge from students' experiences and perceptions regarding social media use. The results of the research, firstly, are impressive student experiences where social media can help individuals effectively and efficiently from various activities and jobs so that they can reduce various burdens, both material and non-material. Apart from that, experience in using social media can help individuals maintain good communication without worrying about distance and time. Basically, students are able to adapt and apply something positive when communicating or when using social media so that they can influence the development of their communication psychology with positive and useful things. Students' experience in using social media can still maintain good interactions and improve psychological well-being for students